Molecular detection of Streptococcus agalactiae in pregnant women and percentage of vertical transmission to their neonates in Babylon province - Ali D. Marhash; Zainab N. Nabat; Nawras A. Abbas (Журнал микробиологии, эпидемиологии и иммунобиологии, 2024)
Introduction. Streptococcus agalactiae are gram-positive, non-motile and encapsulated cocci. On blood agar, they produce an narrow zone of beta-haemolysis. This pathogen causes invasive bacterial diseases in newborns, including sepsis, meningitis, septicaemia, and pneumonia, when transmitted from infected mothers. Since S. agalactiae is a pathogen of primary concern for public health, this research has been conducted on it.